THE EFFECT OF USING EQUIVALENT PERFORMANCE GRADE 76 MODIFIED ASPHALT TO RESILIENT MODULUS AND FATIGUE PERFORMANCE OF HOT ROLLED SHEET-WEARING COARSE (HRS-WC) MIXTURE - ALIA AYESHA (NIM : 26914005), AGHNIA
Early failure that frequently happening to the pavement structure are mostly caused by over load, high surface temperatures, or poor mixture quality of asphalt. Therefore, it is necessary to have asphalt with a better performance, compared to conventional asphalt. By using the performance grade, asphalt system is expected to produce a better pavement structure. Asphalt mixture used in this study was HRS-WC with 60/70 pen asphalt and equivalent to the performance grade 76 (SPG76) modified asphalt as a binder. The objective of this research is to determine Resilient Modulus and Fatigue performance of modified asphalt SPG76 from HRS-WC mixture. Furthermore, the performance of Resilient Modulus was measured by UMATTA and Fatigue performance was measured using Four Point Loading Test. Resilient Modulus test results shown that at low temperature Resilient Modulus value of SPG76 modified asphalt mixture lower than pen 60/70 asphalt mixture. While at higher temperatures (above 51C), SPG76 modified asphalt mixture has Resilient Modulus value higher than pen 60/70 asphalt mixture. It shows that the SPG76 modified asphalt mixture has better crack resistance at low temperatures and at high temperatures will be more resistance to permanent deformation. Fatigue test shown that SPG76 modified asphalt mixture has better fatigue resistance than pen 60/70 asphalt mixture and Marshall immersion test shown that SPG76 modified asphalt mixture has better performance than pen 60/70 asphalt mixture.